2015
DOI: 10.1088/1674-1056/24/1/010501
|View full text |Cite
|
Sign up to set email alerts
|

Neural adaptive chaotic control with constrained input using state and output feedback

Abstract: Neural adaptive chaotic control with constrained input using state and output feedback * Gao Shi-Gen(高士根) a) , Dong Hai-Rong(董海荣) a) † , Sun Xu-Bin(孙绪彬) b) , and Ning Bin(宁 滨) a) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…For a nonlinear system with input constraints [3,4], an event-triggered-based non-zero-sum (NZS) game approximate optimal control method based on integral reinforcement learning (IRL) is proposed in this paper to solve the trajectory tracking control problem. For the nonlinear system with input constraints, Gao et al [5] developed a class of adaptive control methods with input constraints and constructed an auxiliary system to maintain the stability. Meng et al [6] suggested a cooperative control method for a multi-agent system, which transformed the constrained tracking control issues into an unconstrained output feedback control problem.…”
Section: Introductionmentioning
confidence: 99%
“…For a nonlinear system with input constraints [3,4], an event-triggered-based non-zero-sum (NZS) game approximate optimal control method based on integral reinforcement learning (IRL) is proposed in this paper to solve the trajectory tracking control problem. For the nonlinear system with input constraints, Gao et al [5] developed a class of adaptive control methods with input constraints and constructed an auxiliary system to maintain the stability. Meng et al [6] suggested a cooperative control method for a multi-agent system, which transformed the constrained tracking control issues into an unconstrained output feedback control problem.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, owing to the development of computer technology, many algorithms of neural networks arise at the historic moment and have attracted broad attention. [27][28][29][30][31][32] Among them, RBF neural networks have shown great computational superiority in solving various partial differential equations, [33][34][35][36] especially the FPK equation. [37,38] Wang et al proposed the use of the RBF neural networks to calculate the transient solutions of FPK equations [38] and first-passage problems [37] in random vibrations, setting up a great wave of solving nonlinear random vibration problems.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Lots of control methods have been developed, such as the impulsive control method, [3][4][5] the adaptive dynamic programming method, [6,7] and neural adaptive control method. [8] In addition, the optimal tracking control problem is often encountered in the industrial process, and so it has recently been the research focus of many researchers. [9][10][11] In recent years, the adaptive dynamic programming (ADP) method has attracted a great deal of attention in the control field, which is one of the most useful intelligent control methods for solving nonlinear Hamilton-Jacobi-Bellman (HJB) equations.…”
Section: Introductionmentioning
confidence: 99%